Queer Ecologies of Overflow: Bodies-Territory in Dispute in the Face of Extractivism - Rincón Soto, Idana Beroska (2026)
This essay proposes a critical reading of modern nature from queer ecologies located in Latin America. Instead of understanding queer as a fixed identity, it is approached as an onto-epistemic power capable of overflowing the colonial regimes that separate nature/culture, body/territory and knowledge/desire. It is argued that extractivism operates as a rationality of material, epistemic, and ontological dispossession that reconfigures territories and corporalities through economies that produce available, useful, or disposable lives. In contrast to this, the notion of pedagogies of overflow is developed: critical practices that do not replace dispossession with its opposite, but reveal its ambivalences and surpluses, enabling modes of multispecies cohabitability, dissident care, and economies of bonding. By articulating Latin American queer thought, decolonial feminisms, indigenous cosmopolitics, and critical ecologies, the text argues that queer ecologies are not a supplement to environmental diversity, but a vital commitment to re-existences that disrupt the boundaries between body, desire, territory, and life.